THE ROLE OF FLIPPED CLASSROOM AND INTERACTIVE LEARNING IN DEVELOPING STUDENTS’ ARTISTIC AND AESTHETIC COMPETENCIES - Boboniyozova Roziya Mirsalim qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores the effectiveness of flipped classroom and interactive learning strategies in developing students’ artistic and aesthetic competencies in visual arts education. The study highlights how these methods promote active engagement, independent learning, critical thinking, and creative expression. Drawing upon research by Shovdirov S.A. and other scholars, the article demonstrates that integrating flipped classrooms and interactive approaches enhances students’ artistic competence, aesthetic awareness, and motivation, thereby improving the overall quality of art education.